Dissociative disorders among male inpatients with alcohol dependency - Taner, Ender; Açıkyürek, Kardem; Coşar, Behçet; Arıkan, Zehra (Journal of Dependence, 2007)
Objective: The aim of this study is to investigate the prevalence of dissociative disorders and their probable relationship with environmental and sociodemographic factors in in-patients with alcohol dependency.Method: Seventy eight consequtive in-patients with alcohol dependency were who were hospitalised in Alcohol dependency unit of Gazi University, Psychiatry Department were recruited in the study. All patients were required to be alcohol free for at least 3 weeks. All patients completed the sociodemographic data form, dissociative experience scale (DES), dissociation scale (DS) and somatic dissociation scale (SDS).Results: DES, DS and SDS scores of the patients were 1.95±0.68, 20.66±15.67, 32.08±12.18 respectively. With regard to cut-off scores of the scales 11 (14.1%) patients had dissociation in each of the scales and 20 (25.6%) patients had dissociation in any of the scales. There were no relation between age at onset of alcohol dependency, education level, marital status, history of psychiatric disorder, family history of dependency and dissociative symptoms (p>0.05). Patients with a history of drug abuse or current nicotine dependency had higher scores in DS and SDS than the patients without a history of drug abuse or current nicotine dependency.Conclusion: Dissociative symptoms were present in 25.6% of the patients with alcohol dependency in this sample which indicates that dissociation is a major problem in one out of four patients with alcohol dependency. Problem of dissociation was even more in patients with a history of drug abuse or current nicotine dependency. Other studies are needed to clarify the reasons underlying high prevalence of dissociation in patients with alcohol dependency.
Keywords: Alcohol dependency; nicotine dependency; dissociation; dissociative experience scale; DES; somatoform dissociation questionnaire (SDQ); dissociation questionnaire (DIS-Q)